Effect of Surface Roughness on Adhesive Bonding of Aluminum AA3105-H12 with oxygen-free High conductivity Copper C10200 - Salih, Darya Sarwar M. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The effect of 4 different surface roughnesses with 4 different assembling cases on shear bond strength of bonding Aluminum AA3105-H12 with oxygen-free High Conductivity Copper C10200 was examined. The results demonstrated that the highest shear bond strengths with the highest surface roughness were obtained, and then decreases with the increasing of the value of emery paper grade. The result of bonding similar specimens shows that the Aluminum specimens recoded the highest shear bond strength (13.8 MPa at emery paper grade ASTM 400) than the OFHC Copper specimens (10.33 MPa at emery paper grade ASTM 400). The result of bonding dissimilar specimens recoded that the group (Al-Cu-Al) has the highest shear bond strength (12.33 MPa at emery paper grade ASTM 400) than the group (Cu-Al-Cu) which has (6.02 MPa at emery paper grade ASTM 400). And that shows that the shear bond strength varied with the metals used. However, the shear bond strength value varied with the type of metals used and the surface roughness.
Keywords: Adhesive bonding; Surface roughness; Shear bond strength